(untitled) (KULT_online, 2012)
It has become a matter of consensus in the humanities that historical narratives build upon experience as well as convey, revise, and critically test experience, even if concrete forms of historiographical, literary-fictional, or autobiographical writing approach this subject in different ways. It is even more gratifying, then, that the editors of and the contributors to the conference proceedings Erfahrung und Geschichte (Experience and History) have embarked on specifying the notion of experience in the context of historical narration and that they, through a broad spectrum of disciplinary contributions, have managed to cover an interdisciplinary field so far insufficiently explored. The editors of the collection refer to the recently prominent ’experiential turn,’ which has brought the notion of experience to the forefront of discussions of history and memory, and which underlies the concept of this collection. The editors systematically ground the ’prenarrative’ mentioned in the subtitle in a phenomenological manner. Their essay doesn’t, however, manage to cover the variety of possibilities offered by ’experience’ in relation to ’history’ presented in the contributions, which focus above all on the analysis of historical experience in different narratives.